Effect of DIN and DON sources on the nitrogen uptake of the seagrass Zostera japonica and the macroalgae Ulva pertusa previously grown in different light levels - Han, Qiuying; Qiu, Chongyu; Zeng, Wenxuan; Chen, Yu; Zhao, Muqiu; Shi, Yunfeng; Zheng, Fengying (Frontiers in Marine Science, 2023)
This study quantified the absorption ability of the seagrass Zostera japonica and macroalgae Ulva pertusa for dissolved inorganic nitrogen (DIN, ammonium and nitrate) and dissolved organic nitrogen (DON, urea and glycine) after different light conditions. The plants were cultured in filtered seawater (31‰, 25 °C) for two weeks under three light levels. Macroalgae, aboveground parts and belowground parts of seagrasses were separately placed into four different man-made seawater solutions with DIN (ammonium, nitrate) and DON (urea, glycine) stable isotope for one hour. Our results showed that macroalgae had higher absorption rate to ammonium and nitrate after higher light treatments (14.67±2.50 mg-1 DW h-1, 1.29±0.16 mg-1 DW h-1) than lower light treatments (4.52±0.95 mg-1 DW h-1, 0.18±0.12 mg-1 DW h-1), respectively. Under comparison to belowground seagrass portions that had previously been grown in high and low light conditions, the seagrass leaves assimilate ammonium more quickly. Z. japonica preferred glycine to nitrate and urea after the high- and low- light treatments. That is, the absorption rate of belowground seagrass parts to glycine was 14.71±1.85 and 6.38±0.52 mg-1 DW h-1 after high- and low- light treatments, respectively, which was higher than ammonium, nitrate, and urea. The absorption rate of algae was lower than that of ammonium previously grown under medium- and low-light treatments. Our results indicated that light reduction can impact the assimilation of DIN by Z. japonica and U. pertusa, and both have the ability to directly assimilate DON. This study provides information to reduce the negative effects of eutrophication on macroalgae and seagrasses in order to protect seagrass meadows.